Method for producing solid particle
Patent Information
- Application Number
- JP2022103982
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-30
- Filing Date
- 2022-06-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-06-28
AI Technical Summary
Existing methods for producing granular solid cosmetics result in residual liquid oil on the surface, leading to adhesion issues, deformation during transportation, and impaired usability due to hardness.
A method involving heating a raw material composition with an oily component to impart fluidity, granulating it, and coating the surface of the granules with powder while vibrating to create a core-shell structure, enhancing adhesion resistance and usability.
The method produces solid particles with improved transportation resistance and usability by preventing adhesion and deformation, while maintaining a desirable feel during use.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing solid particles and to solid particles themselves. [Background technology]
[0002] Solid particles, such as those found in solid cosmetics, have generally been in the form of compressed powder contained in a shallow tray, like foundation, or in the form of a solid composition molded into a predetermined shape at room temperature, like lipstick. In addition to these forms of solid cosmetics, granular solid cosmetics have recently been proposed.
[0003] For example, Patent Document 1 describes a method for obtaining a granular solid cosmetic product with an average particle size of 1 to 5 mm by dropping a liquefied cosmetic product into a liquid oil that is incompatible with the cosmetic product to form it into granules, then lowering the temperature of the granular cosmetic product to solidify it, and finally separating it from the liquid oil. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2009-274974 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] The granular solid cosmetic described in Patent Document 1 uses liquid oil in its manufacturing process, so if the liquid oil is not sufficiently separated, liquid oil will remain on the surface of the granular solid cosmetic. As a result, the granular solid cosmetic may adhere to the container or the granular solid cosmetic particles may easily stick together, reducing its adhesion resistance. Furthermore, simply granulating a solid cosmetic such as lipstick makes it vulnerable to impacts during transportation, and it easily deforms and clumps together. Increasing the hardness of the solid cosmetic makes it more resistant to transportation, but the hardness impairs the feel of the product when used.
[0006] This invention relates to a method for producing solid particles that are excellent in terms of transport resistance while satisfying both adhesion resistance and usability. Adhesion resistance means that adhesion between the solid particles and the container, as well as adhesion and bonding between the solid particles themselves, are suppressed. [Means for solving the problem]
[0007] The inventors have discovered that by granulating a raw material composition containing an oily component that has been given fluidity by heating, bringing the granulated raw material composition into contact with powder, and coating the surface of the granular raw material with powder while applying vibration to the powder during contact, solid particles can be obtained that satisfy adhesion resistance and usability while also having excellent transport resistance. The present invention relates to the following [1] and [2]. [1] A method for producing solid particles comprising the following steps 1 to 3, Step 1: A step of heating the raw material composition containing oily components to impart fluidity. Step 2: A step of granulating the raw material composition to which fluidity has been imparted in order to obtain granular raw material. Step 3: A step of bringing the granular raw material and the powder into contact and coating the surface of the granular raw material with the powder. A method for producing solid particles, wherein the contact is performed while the powder is subjected to vibration. [2] Solid particles having a core portion made of a raw material composition and a shell portion covering at least a part of the surface of the core portion, wherein the shell portion is made of a raw material composition incorporating powder, and the thickness of the raw material composition incorporating powder is 110 μm or more, the solid particles having a core-shell structure. [Effects of the Invention]
[0008] According to the manufacturing method of the present invention, it is possible to provide solid particles that are excellent in terms of transport resistance while satisfying the requirements for adhesion resistance and usability. [Brief explanation of the drawing]
[0009] [Figure 1] Figure 1 is a schematic diagram showing one embodiment of the invention using a vibratory feeder. [Figure 2] Figure 2 is a schematic diagram showing an embodiment of the present invention by a bowl feeder. [Figure 3] Figure 3 is a diagram showing the result of observing a cross-section of solid particles of an embodiment of the present invention with an electron microscope. [Figure 4] Figure 4 is a diagram showing the result of observing a cross-section of solid particles of a comparative example with an electron microscope.
Mode for Carrying Out the Invention
[0010] Hereinafter, the present invention will be described based on its preferred embodiments with reference to the drawings. The present invention relates to a method for producing solid particles.
[0011] [Solid Particles] The solid particles of the present invention are solid particles having a core-shell structure, which comprises a core part made of a granular solid raw material composition and a shell part covering at least a part of the surface of the core part. The shell part is composed of a layer of a raw material composition incorporating powder. Although it also depends on the properties of the powder and the production conditions, the powder is incorporated into the raw material composition from the surface of the core part with a thickness of about 100 μm, for example. The solid particles of the present invention are preferably produced by the method for producing solid particles of the present invention described below. Since the strength in the vicinity of the surface of the solid particles of the present invention is improved by the adhesion of the powder and the incorporation into the raw material composition, it is considered that the crushing of the solid particles due to the contact between the particles or between the particles and the container during transportation can be suppressed. Thereby, the exposure of the core part can be suppressed and the adhesion between the solid particles can be suppressed, so that it is considered to have excellent transportation resistance. Furthermore, since the powder exists in the vicinity of the surface, the deterioration of the usability can be suppressed. The "solid particles" are particles that are solid at room temperature (25°C) and have the property of softening or melting and obtaining fluidity when heated to a temperature higher than room temperature, for example, 50°C or higher. Particles formed by compression molding of powder are excluded from the solid particles referred to in the present invention. To obtain such solid particles, for example, a raw material composition having a melting point of 50°C or higher may be used as described below. The term "particle" includes not only spherical or substantially spherical shapes, but also flat, spindle-shaped, polyhedral, fibrous shapes, and irregular shapes. Furthermore, it includes shapes resembling some characters or symbols, as well as shapes resembling characters such as people, animals, and objects. The solid particles of the present invention can be one of these shapes or a combination of two or more of them.
[0012] 〔Shape of Solid Particles〕 The solid particles are not particularly limited in size, but from the viewpoints of ease of use such as being easy to handle, difficulty in rolling, ease of crushing, designability, and ease of manufacture, etc., the average projected area when placed on a plane is preferably 0.5 mm 2 or more, more preferably 1 mm 2 or more, still more preferably 1.5 mm 2 or more. Also, from the viewpoints of ease of use such as being easy to handle, ease of crushing, and designability, etc., the average projected area of the solid particles is preferably 320 mm 2 or less, more preferably 80 mm 2 or less, still more preferably 20 mm 2 or less. In particular, the average projected area of the solid particles is preferably 0.5 mm 2 or more and 320 mm 2 or less, more preferably 1 mm 2 or more and 80 mm 2 or less, still more preferably 1.5 mm 2 or more and 20 mm 2 or less. The "average projected area" means the number average value of the areas projected onto the horizontal plane with respect to light from directly above in the state where 10 solid particles randomly extracted are placed in the most stable state on the horizontal plane.
[0013] When the solid particles are spherical or substantially spherical, their diameter is preferably 0.5 mm or more, more preferably 1 mm or more, even more preferably 1.5 mm or more, and preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less. The diameter of spherical or substantially spherical solid particles is preferably 0.5 mm or more and 20 mm or less, more preferably 1 mm or more and 10 mm or less, and even more preferably 1.5 mm or more and 5 mm or less. Furthermore, when the solid particles are oblate or nearly oblate, their diameter is the equivalent circle diameter determined from the horizontal projection, preferably 0.5 mm or more, more preferably 1 mm or more, even more preferably 1.5 mm or more, and preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less. The diameter of the oblate or nearly oblate solid particles is preferably 0.5 mm or more and 20 mm or less, more preferably 1 mm or more and 10 mm or less, and even more preferably 1.5 mm or more and 5 mm or less. Furthermore, when the solid particles are oblate or nearly oblate, their height is the distance between the surface in contact with the solid particles, which is horizontal to the horizontal plane on which the solid particles are placed and is located at the furthest point from the horizontal plane, and preferably 0.4 mm or more, more preferably 0.8 mm or more, even more preferably 1.2 mm or more, and preferably 16 mm or less, more preferably 8 mm or less, and even more preferably 4 mm or less. The height of the oblate or nearly oblate solid particles is preferably 0.4 mm or more and 16 mm or less, more preferably 0.8 mm or more and 8 mm or less, and even more preferably 1.2 mm or more and 4 mm or less.
[0014] The average mass per solid particle is preferably 1 mg or more, more preferably 5 mg or more, and even more preferably 10 mg or more. Furthermore, the mass per solid particle is preferably 10,000 mg or less, more preferably 5,000 mg or less, and even more preferably 1,000 mg or less. The mass of the solid particles is preferably 1 mg or more and 10,000 mg or less, more preferably 5 mg or more and 5,000 mg or less, and even more preferably 10 mg or more and 1,000 mg or less. "Average mass" refers to the numerical average of the masses of 10 randomly selected solid particles.
[0015] The average strength per solid particle is preferably 0.14N or higher, more preferably 0.16N or higher, from the viewpoint of transport resistance. Furthermore, the average strength per solid particle is preferably 3N or lower, more preferably 1N or lower, from the viewpoint of usability. The average strength of the solid particles is preferably 0.14N or higher and 3N or lower, more preferably 0.16N or higher and 1N or lower. "Average strength" refers to the numerical average of the strengths of 10 randomly selected solid particles. The strength of the solid particles is measured by the method described in the examples.
[0016] [Solid particle manufacturing method] The present invention provides a method for producing solid particles, comprising the following steps 1 to 3: Step 1: A step of heating the raw material composition containing oily components to impart fluidity. Step 2: A step of granulating the raw material composition to which fluidity has been imparted in order to obtain granular raw material. Step 3: A step of bringing the granular raw material and the powder into contact and coating the surface of the granular raw material with the powder. The aforementioned contact is performed while the powder is subjected to vibration.
[0017] An example of a method for producing solid particles according to the present invention will be described below with reference to Figure 1. Step 1 is a step of obtaining a raw material composition 10 by heating the raw material composition to impart fluidity. Step 2 is a step of obtaining granular raw material 13 by granulating the raw material composition 10 to which fluidity has been imparted. In Figure 1, the raw material composition 10 to which fluidity has been imparted is conveyed using a pump 11 and granulated by being discharged from the tip of a nozzle 12 to obtain granular raw material 13. Furthermore, step 3 is a step of coating the surface of the granular raw material 13 with powder 14 by bringing the granular raw material 13 into contact with the powder 14 while the powder 14 is being vibrated, causing the powder 14 to adhere to the granular raw material 13. In Figure 1, vibration is applied to the powder 14 on the trough 16 by using a vibrating feeder 19 in which a trough 16 is installed on a vibrating device 15. Preferably, the solid particles 1 produced through steps 1 to 3 are conveyed on the trough 16 and separated from the powder 14 by a sieve 17. In the manufacturing method of the present invention, when the powder 14 adheres to the granular raw material 13, it means not only that the powder 14 adheres to the surface of the granular raw material 13, but also that some of the powder 14 is incorporated into the interior of the granular raw material 13 near its surface. For example, the powder 14 is incorporated to a depth of about 100 μm from the surface of the granular raw material 13. Furthermore, in the manufacturing method of the present invention, coating the surface of the granular raw material 13 with powder 14 means not only that the entire surface of the granular raw material 13 is covered with powder 14, but also that at least a portion of the surface of the granular raw material 13 is covered with powder 14. From the viewpoint of improving adhesion resistance and transport resistance, it is preferable that the entire surface of the granular raw material 13 is covered with powder 14.
[0018] Furthermore, as shown in Figure 2, a bowl 18 may be used instead of a trough 16 as the container for the powder 14. By using a bowl feeder 20 in which a bowl 18 is installed on a vibrating device 15, vibration is applied to the powder 14 inside the bowl 18. The granular raw material 13 that comes into contact with the vibrating powder 14 has its surface covered with the powder 14 and rises up the slope provided on the inner wall of the bowl 18 due to the vibration. When increasing the contact time between the granular raw material 13 and the powder 14, it is necessary to lengthen the trough 16, but when using a bowl 18, it is only necessary to extend the number of turns of the spiral in the height direction, which is space-efficient.
[0019] [Process 1] Step 1 is a step of heating a raw material composition containing an oily component to impart fluidity. By heating the raw material composition to a temperature above the melting point of at least one substance it contains, a raw material composition 10 with imparted fluidity can be obtained. It is also preferable to heat the raw material composition to a temperature above its melting point. The temperature for imparting fluidity to the raw material composition is preferably 60°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and still more preferably 85°C or higher, from the viewpoint of delaying the solidification of the granular raw material 13 and promoting the adhesion of the powder 14 in step 3. Furthermore, from the viewpoint of preventing deterioration of the raw material composition due to heat, the temperature is preferably 150°C or lower, more preferably 130°C or lower, even more preferably 120°C or lower, and still more preferably 115°C or lower. In particular, the temperature for imparting fluidity to the raw material composition is preferably 60°C to 150°C, more preferably 70°C to 130°C, even more preferably 80°C to 120°C, and still more preferably 85°C to 115°C.
[0020] Furthermore, the raw material composition 10 to which fluidity has been imparted may be in the form of a paste (semi-solid) in which the heated raw material composition has not completely melted. A paste-like raw material composition is preferable because it has a certain degree of viscosity, which allows it to be formed into the desired shape when obtaining granular raw material in the next step, step 2.
[0021] [Process 2] Step 2 is a step in which the fluidized raw material composition 10 is granulated to obtain granular raw material 13. If the fluidized raw material composition 10 shown in Figure 1 is a liquid obtained by heating the raw material composition above its melting point, the raw material composition delivered by the pump 11 is discharged from the tip of the nozzle 12, thereby obtaining granular raw material 13 as droplets. If the fluidized raw material composition 10 is in paste form, it is extruded from the tip of the nozzle 12 by the pump 11, thereby obtaining granular raw material 13 having the cross-sectional shape of the tip of the nozzle 12. Furthermore, the apparatus for converting the fluidized raw material composition 10 into granular raw material 13 is not limited to the apparatus shown in Figure 1, and known droplet manufacturing apparatuses, extrusion granulators, etc., can be used.
[0022] The size of the granular raw material 13 obtained in step 2 is approximately the same as the combined size of the core portion of the solid particle, which is the target of the manufacturing method of the present invention, and the shell portion, which consists of a layer of raw material composition incorporating powder covering the core portion. In other words, it is preferable that the granular raw material 13 is adjusted so that the size of the resulting solid particle 1 is within the range, diameter, and / or weight represented by the average projected area when placed on the above-mentioned plane. For this purpose, for example, when granular raw material 13 is obtained as droplets by discharging a liquid raw material composition 10 from the tip of a nozzle 12, the inner diameter of the nozzle 12 can be changed according to the particle size of the desired solid particles. From the viewpoint of obtaining a particle size corresponding to the amount of solid particles used per application, the inner diameter of the nozzle 12 is preferably 0.5 mm or more, more preferably 1 mm or more, and even more preferably 1.5 mm or more. Also, from the viewpoint of stably dropping the granular raw material 13, it is preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less. In particular, the inner diameter of the nozzle 12 is preferably 0.5 mm or more and 20 mm or less, more preferably 1 mm or more and 10 mm or less, and even more preferably 1.5 mm or more and 5 mm or less. Furthermore, if the fluidized raw material composition 10 is in paste form, granular raw material 13 corresponding to the desired size and weight of solid particles can be obtained by cutting the raw material composition 10 extruded from the tip of the nozzle 12 into predetermined sizes.
[0023] [Step 3] Step 3 is a step in which the granular raw material 13 and the powder 14 are brought into contact, and the surface of the granular raw material 13 is coated with the powder 14. The contact between the granular raw material 13 and the powder 14 is carried out while the powder 14 is subjected to vibration. When the contact between the granular raw material 13 and the powder 14 is carried out while the powder 14 is subjected to vibration, it is thought that the powder 14 can be incorporated to a depth of at least 80 μm from the surface of the granular raw material 13, and solid particles with excellent adhesion resistance and transport resistance can be obtained.
[0024] As shown in Figure 1, it is preferable that the granular raw material 13 and the powder 14 come into contact by dropping or dropping the granular raw material 13 onto the powder 14 on a trough 16 installed on a vibrating device 15. Furthermore, it is preferable that the powder 14 is continuously supplied onto the trough 16 by a powder supply device (not shown). The distance at which the granular raw material 13 is dropped or dropped, that is, the distance between the tip of the nozzle 12 and the outermost surface of the powder layer 14, is preferably 35 cm or less, more preferably 25 cm or less, and even more preferably 15 cm or less, from the viewpoint of mitigating the impact when the dropped or dropped granular raw material 13 comes into contact with the powder 14, preventing deformation, and suppressing the cooling of the granular raw material 13 during dropping or dropping. The thickness of the powder layer 14 is preferably 3 mm or more, more preferably 5 mm or more, and even more preferably 8 mm or more, from the viewpoint of promoting adhesion of the powder 14 to the top of the dropped or fallen granular raw material 13. Furthermore, from the viewpoint of avoiding the use of excessive powder, the thickness of the powder layer 14 is preferably 50 mm or less, more preferably 30 mm or less, even more preferably 20 mm or less, and even more preferably 15 mm or less.
[0025] When the powder 14 is brought into contact with the surface of the granular raw material 13, the amplitude of the vibration applied to the powder 14 is preferably 0.3 mm or more, more preferably 0.4 mm or more, even more preferably 0.5 mm or more, even more preferably 0.6 mm or more, and even more preferably 0.8 mm or more, from the viewpoint of promoting adhesion of the powder 14 to the surface of the granular raw material 13. Furthermore, it is preferably 5 mm or less, more preferably 4 mm or less, even more preferably 3 mm or less, even more preferably 1.5 mm or less, even more preferably 1.4 mm or less, and even more preferably 1.3 mm or less. In particular, the amplitude of the vibration is preferably 0.3 mm to 5 mm, more preferably 0.4 mm to 4 mm, even more preferably 0.5 mm to 4 mm, even more preferably 0.5 mm to 3 mm, even more preferably 0.6 mm to 3 mm, even more preferably 0.8 mm to 3 mm, even more preferably 0.3 mm to 1.5 mm, even more preferably 0.4 mm to 1.4 mm, even more preferably 0.5 mm to 1.3 mm, and even more preferably 0.6 mm to 1.3 mm. Furthermore, it is preferable to measure the amplitude of the vibration applied to the powder 14 at a position directly above the vibration device 15. Furthermore, from the viewpoint of promoting the adhesion of powder 14 to the surface of granular raw material 13, the vibration frequency is preferably 30 Hz or higher, more preferably 40 Hz or higher, and even more preferably 50 Hz or higher. And preferably 300 Hz or lower, more preferably 100 Hz or lower, even more preferably 75 Hz or lower, and even more preferably 60 Hz or lower. In particular, the vibration frequency is preferably 30 Hz or higher and 300 Hz or lower, more preferably 40 Hz or higher and 100 Hz or lower, even more preferably 50 Hz or higher and 75 Hz or lower, and even more preferably 50 Hz or higher and 60 Hz or lower.
[0026] From the viewpoint of delaying the solidification of the granular raw material 13 and promoting the adhesion of the powder 14, the temperature of the powder 14 is preferably 5°C or higher, more preferably 15°C or higher, and even more preferably 20°C or higher. Also, from the viewpoint of suppressing excessive adhesion of the powder 14 to the granular raw material 13, the temperature of the powder 14 is preferably 60°C or lower, more preferably 55°C or lower, and even more preferably 50°C or lower. In particular, the temperature of the powder 14 is preferably 5°C to 60°C, more preferably 15°C to 55°C, and even more preferably 20°C to 50°C. Furthermore, the temperature of the powder 14 when it is brought into contact with the surface of the granular raw material 13 is preferably room temperature (20°C to 30°C).
[0027] From the viewpoint of promoting the adhesion of the powder to the surface of the granular raw material 13, the contact time between the granular raw material 13 and the powder 14 is preferably 2 seconds or more, more preferably 3 seconds or more, and even more preferably 4 seconds or more. Also, from the viewpoint of productivity, the contact time between the granular raw material 13 and the powder 14 is preferably 30 seconds or less, more preferably 15 seconds or less, and even more preferably 10 seconds or less. In particular, the contact time between the granular raw material 13 and the powder 14 is preferably 2 seconds or more and 30 seconds or less, more preferably 3 seconds or more and 15 seconds or less, and even more preferably 4 seconds or more and 10 seconds or less.
[0028] Through the above step 3, the powder 14 is attached to the surface of the granular raw material 13, and solid particles 1 can be obtained by coating the surface of the granular raw material 13 with the powder 14. Simultaneously with and / or after step 3, there may be an additional step of cooling the granular raw material 13. Cooling can make the attachment of the powder 14 to the granular raw material 13 even more reliable. Cooling may be, for example, natural cooling or forced cooling. When natural cooling is used, the solid particles 1, whose surface is coated with powder 14 over the granular raw material 13, should be left standing at room temperature. For forced cooling, one can blow gas onto the solid particles 1, leave the solid particles 1 undisturbed in a refrigerator, or bring the solid particles 1 into contact with a refrigerant.
[0029] At the point when the powder 14 is brought into contact with the surface of the granular raw material 13, the granular raw material 13 is softened. The granular raw material 13, whose surface is coated with powder 14, solidifies at one of the subsequent stages. "Solidification" means that the hardness of the granular raw material 13 becomes the hardness of the raw material composition before it is given fluidity by cooling.
[0030] The portion of the solid particle 1 that does not contain the powder 14 obtained by solidifying the granular raw material 13 is the core portion of the solid particle 1. The granular raw material 13 is obtained by granulating the raw material composition and is in its state before solidification. Furthermore, the portion inside the granular raw material 13 near the surface in which the raw material composition has incorporated the powder 14 is the shell portion of the solid particle 1.
[0031] After step 3, the powder 14 that is not adhering to the surface of the solid particles 1 can be removed prior to, after, or simultaneously with the cooling of the solid particles 1. The powder 14 that is not adhering to the surface of the solid particles 1 refers to powder 14 that is weakly attached to the solid particles 1 to the extent that it falls off due to external forces such as vibrations applied when the solid particles 1 are transported, or powder 14 that is not attached at all to the parts derived from the raw material composition.
[0032] To remove the powder, a sieve 17 with a mesh size that does not allow solid particles 1 to pass through can be used, as shown in Figure 1. The thickness of the shell portion of the solid particles 1 after powder removal is preferably 80 μm or more, more preferably 100 μm or more, even more preferably 110 μm or more, even more preferably 120 μm or more, even more preferably 130 μm or more, and even more preferably 150 μm or more, from the viewpoint of improving adhesion resistance and transport resistance. In particular, a shell portion thickness of 110 μm or more is preferable because it further improves the adhesion resistance and transport resistance of the solid particles 1. Furthermore, from the viewpoint of suppressing a decrease in usability, it is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less.
[0033] From the viewpoint of improving adhesion resistance and transport resistance, the proportion of powder incorporated into the solid particles 1 after the removal of the powder is preferably 5.0% by mass or more, more preferably 7.0% by mass or more, even more preferably 7.5% by mass or more, and even more preferably 8.0% by mass or more, relative to the mass of the solid particles. Furthermore, from the viewpoint of not affecting the feel of use, it is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, even more preferably 13% by mass or less, and even more preferably 12% by mass or less.
[0034] The solid particles produced by the manufacturing method of the present invention have anti-adhesion properties because the surface of the core portion is covered with a shell portion containing powder. Therefore, even if the core portion is sticky, for example, this stickiness is reduced by the shell portion containing powder, thus preventing unintended adhesion of the solid particles to the conveying equipment during transport. Furthermore, when filling the solid particles into a container, for example, it is prevented that the solid particles will not unintendedly adhere to the inner wall or lid of the container, reducing the filling efficiency, and after filling the container, it is prevented that the solid particles will not unintendedly adhere to the inner wall or other solid particles of the container, reducing the ease of removal from the container. On the other hand, the strength of the solid particles themselves is improved not only by adhesion to the surface of the solid particles, but also by the incorporation of powder into the interior near the surface of the solid particles, improving resistance to impact during transport. Moreover, because the powder is localized in the shell portion near the surface of the solid particles, the actual powder content contained in the solid particles is reduced, resulting in a good user experience. For this reason, the solid particles produced by the manufacturing method of the present invention have anti-adhesion properties, making it possible to achieve both transport resistance and a good user experience.
[0035] [Raw materials for solid particles] [Raw material composition] The raw material composition is solid at room temperature (25°C) and has a melting point preferably of 50°C or higher, more preferably of 55°C or higher, and even more preferably of 60°C or higher. Since the granular raw material obtained by granulating the raw material composition becomes the core of the solid particles, having a melting point of the raw material composition above this temperature can improve the feel when the solid particles are used as a cosmetic. Furthermore, from the viewpoint of ease of manufacture, the melting point of the raw material composition is preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 110°C or lower. Having a melting point below this temperature can also improve the feel of the solid particles. In particular, the melting point of the raw material composition is preferably 50°C to 150°C, more preferably 55°C to 120°C, and even more preferably 60°C to 110°C.
[0036] Raw material compositions typically contain multiple substances. In this case, the melting point of the raw material composition is measured using one of the following methods: Method 1, Method 2, or Method 3 of the General Test Methods for Quasi-Drug Raw Material Standards. The choice of method is primarily determined by the melting point of the raw material composition. Method 1 can be used if the melting point is high, exceeding 75°C; Method 2 can be used if the melting point is between 50°C and 75°C; and Method 3 can be used if the melting point is below 50°C.
[0037] The raw material composition is preferably a cosmetic raw material composition, from the viewpoint that the solid particles of the present invention are preferably used as a cosmetic. The raw material composition preferably has a continuous phase consisting of one or more oily components. In some cases, the raw material composition contains powder components such as pigments dispersed in the continuous phase. Examples of oily components include hydrocarbon oils, ester oils, ether oils, fatty acids, alcohols, silicone oils, and fluorine oils. The number of carbon atoms in the oily components is preferably 6 or more, more preferably 10 or more, preferably 50 or less, and more preferably 30 or less. Specifically, these include mineral waxes such as ozokerite and ceresin; petroleum waxes such as paraffin and microcrystalline wax; synthetic hydrocarbons such as Fischer-Tropsch wax, polyethylene wax, and synthetic waxes; plant waxes such as carnauba wax, candelilla wax, rice wax, sunflower wax, hydrogenated jojoba oil, and Japanese wax; animal waxes such as beeswax and whale wax; synthetic waxes such as silicone wax, synthetic beeswax, and synthetic Japanese wax; oily gelling agents such as dextrin palmitate, sucrose fatty acid ester, inulin stearate, 12-hydroxystearic acid, dibutyl lauroyl glutamide, dibutyl ethylhexanoyl glutamide, and polyamide resins; petrolatum, vinyl leather wax, hexa(behenic acid / benzoic acid / ethylhexanoic acid) dipentaerythrityl, cholesteryl hydroxystearate, tetra(hydroxystearate / isostearate) dipentaerythrityl, and water. Palm oil, dipentaerythrityl hexahydroxystearate, glyceryl tri(caprylate / caprate / myristicate / stearate), dipentaerythrityl hexa(hydroxystearate / stearate / rosinate), phytosteryl oleate, glyceryl (ethylhexanoate / stearate / adipate), di(octyldodecyl / phytosteryl / behenyl) lauroyl glutamate, phytosteryl / isostearyl dimer dilinoleate Paste oils such as cetyl / stearyl / behenyl dimer dilinoleyl bis(behenyl / isostearyl / phytosteryl) dimer dilinoleate, hard lanolin, reduced lanolin, bis-diglyceryl polyacyladipate-2; liquid paraffin, light liquid isoparaffin, heavy liquid isoparaffin, mineral oil, squalane, α-olefin oligomer, polyisobutylene, polybutene, hydrogenated polyisobutene, hydrogenated polydecene, and other linear or branched hydrocarbon oils;Isononyl isononanoate, isodecyl isononanoate, isotridecyl isononanoate, tricyclodecanemethyl isononanoate, ethyl isostearate, isobutyl isostearate, isopropyl isostearate, 2-hexyldecyl isostearate, di-2-ethylhexyl succinate, bisethoxydiglycol succinate, hexyl laurate, di(caprylic / capric acid)propanediol, neopentyl glycol diisononanoate, neopentyl glycol dicaprate, glyceryl diisostearate, polyglyceryl diisostearate , propanediol diisostearate, trimethylolpropane triisostearate, glyceryl triisostearate, diglyceryl triisostearate, diglyceryl tetraisostearate, diisostearyl malate, octyldodecyl malate, glycerin fatty acid ester, jojoba oil, phytosteryl / octyldodecyl lauroyl glutamate, octyldodecyl myristate, isopropyl myristate, 2-ethylhexyl palmitate, isopropyl palmitate, cetyl 2-ethylhexanoate, tri-2-ethylhexa Trimethylolpropane hydroxypropyl alcohol, glyceryl tri-2-ethylhexanoate, octyldodecyl myristate, 2-hexyldecyl myristate, 2-hexyldecyl 2-ethylhexanoate, neopentyl glycol di-2-ethylhexanoate, ethylhexyl hydroxystearate, caprylic / capric triglyceride, glyceryl trioctanoate, neopentyl glycol dioctanoate, tridecyl trimellitate, dipentaerythrityl tetraisostearate, pentaerythrityl tetraisostearate, octyl methoxycinnamate, Ester oils such as 2-ethylhexyl lamethoxycinnamate, diisopropyl dimerate, and propylene carbonate; higher alcohols such as lauryl alcohol, oleyl alcohol, isostearyl alcohol, behenyl alcohol, and octyldodecanol; silicone oils such as dimethylpolysiloxane, dimethylcyclopolysiloxane, methylphenylpolysiloxane, trimethylpentaphenyltrisiloxane, methylhydrogenpolysiloxane, higher alcohol-modified organopolysiloxane, and bisalkyl (C16-18) glycerin undecyl dimethicone;Examples include fluoropolyethers, perfluoroalkyl ether silicones, and fluorine-modified silicones; tocopherol, dipropylene glycol, and phenoxyethanol. These oily components can be used individually or in combination of two or more.
[0038] From the viewpoint of the feel of the solid particles, the raw material composition preferably contains 40% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more of the oily component. From a similar viewpoint, the raw material composition preferably contains 100% by mass or less, more preferably 99% by mass or less, even more preferably 98% by mass or less, even more preferably 97% by mass or less, and even more preferably 95% by mass or less of the oily component. In particular, the raw material composition preferably contains 40% by mass or more and 100% by mass or less, more preferably 50% by mass or more and 99% by mass or less, even more preferably 60% by mass or more and 98% by mass or less, even more preferably 70% by mass or more and 97% by mass or less, and even more preferably 80% by mass or more and 95% by mass or less of the oily component.
[0039] From the viewpoint of improving the shape retention of solid particles, the raw material composition preferably contains an oily component (for example, the wax mentioned above) that is solid at 20°C (with a melting point above 20°C). From the viewpoint of improving the shape retention of solid particles, the raw material composition preferably contains 3% by mass or more, more preferably 5% by mass or more, of the oily component that is solid at 20°C. Furthermore, from the viewpoint of the feel of the solid particles, the oily component that is solid at 20°C preferably contains 30% by mass or less, more preferably 10% by mass or less. In particular, the raw material composition preferably contains 3% by mass or more and 30% by mass or less, more preferably 5% by mass or more and 10% by mass or less, of the oily component that is solid at 20°C. In addition, from the viewpoint of improving the feel of the solid particles, the raw material composition preferably contains an oily component that is liquid at 20°C (with a melting point below 20°C). From this viewpoint, the raw material composition preferably contains 18% by mass or more, more preferably 25% by mass or more, and even more preferably 35% by mass or more, of the oily component that is liquid at 20°C. From a similar viewpoint, the raw material composition preferably contains 97% by mass or less, more preferably 95% by mass or less, and even more preferably 93% by mass or less, of an oily component that is liquid at 20°C. In particular, the raw material composition preferably contains 18% by mass or more and 97% by mass or less, more preferably 25% by mass or more and 95% by mass or less, and even more preferably 35% by mass or more and 93% by mass or less, of an oily component that is liquid at 20°C.
[0040] Whether or not an oily component is liquid at 20°C can be determined by the information provided in the Safety Data Sheet (SDS) and physical condition description for each component. If the raw material composition contains oily components that are liquid at 20°C within the above range, the oily components will be present on the surface of the core portion of the solid particles after manufacturing, which can cause the core portion to easily bond with other materials. In contrast, the solid particles manufactured by the manufacturing method of the present invention have a shell portion covering the surface of the core portion, which suppresses unintended bonding between solid particles or with other materials, thus providing adhesion resistance.
[0041] The powder components included in the raw material composition can be any type of powder conventionally used in cosmetics, without any particular restrictions. The powder components may be inorganic powders or organic powders. Inorganic powders and organic powders may be used in combination. There are no particular restrictions on the shape of the particles constituting the powder components; for example, they may be spherical, polyhedral, flake-shaped, spindle-shaped, fibrous, amorphous, or a combination thereof.
[0042] The powder components included in the raw material composition can be pigments such as coloring pigments, luminosity pigments, and extender pigments, and preferably inorganic powder pigments. Examples of coloring pigments include metal oxides such as titanium dioxide, zinc oxide, yellow iron oxide, red iron oxide, black iron oxide, Prussian blue, ultramarine blue, chromium oxide, and chromium hydroxide; metal complexes such as manganese violet and cobalt titanate; inorganic pigments such as carbon black; synthetic organic pigments such as Red No. 3, Red No. 104, Red No. 106, Red No. 201, Red No. 202, Red No. 204, Red No. 205, Red No. 220, Red No. 226, Red No. 227, Red No. 228, Red No. 230, Red No. 401, Red No. 405, Red No. 505, Orange No. 203, Orange No. 204, Orange No. 205, Yellow No. 4, Yellow No. 5, Yellow No. 401, Blue No. 1, and Blue No. 404; and natural organic pigments such as β-carotene, caramel, and paprika pigment. Examples of luminous pigments include plate-like powders such as mica, synthetic fluorophlogopite, glass, silica, alumina, and talc, coated with colorants such as titanium dioxide, iron oxide, silicon dioxide, Prussian blue, chromium oxide, tin oxide, chromium hydroxide, gold, silver, carmine, and organic pigments such as Red No. 202 and Yellow No. 4; and film rolls such as polyethylene terephthalate / polymethyl methacrylate laminated powder, polyethylene terephthalate / aluminum vapor-deposited powder, and polyethylene terephthalate / gold vapor-deposited laminated powder cut into arbitrary shapes. Examples of extender pigments include inorganic powders such as silica, mica, synthetic fluorophlogopite, glass powder, barium sulfate, kaolin, bentonite, hectorite, zeolite, bismuth oxychloride, zirconium oxide, magnesium oxide, aluminum oxide, calcium sulfate, barium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, and talc. Furthermore, examples include dispersants such as nylon, polyethylene, silicone elastomers such as (vinyl dimethicone / methicone silsesquioxane) crosspolymer, polymethyl methacrylate, lauroyl lysine, silk powder, cellulose powder, polyvalent metal salts of long-chain fatty acids, and organic powders such as various wax powders.
[0043] The proportion of powder components in the raw material composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, even more preferably 3% by mass or more, and even more preferably 5% by mass or more. Furthermore, the proportion of powder components in the raw material composition is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, even more preferably 30% by mass or less, and even more preferably 20% by mass or less. In particular, the proportion of powder components in the raw material composition is preferably 0.01% by mass or more and 60% by mass or less, more preferably 0.1% by mass or more and 50% by mass or less, even more preferably 1% by mass or more and 45% by mass or less, even more preferably 3% by mass or more and 30% by mass or less, and even more preferably 5% by mass or more and 25% by mass or less.
[0044] The hardness of the core is one of the factors that affects the feel of the solid particles. From this viewpoint, the hardness of the raw material composition is preferably 500g or less, more preferably 350g or less, even more preferably 250g or less, and even more preferably 150g or less. On the other hand, by setting the hardness of the raw material composition to preferably 0.5g or more, more preferably 5g or more, and even more preferably 15g or more, unintended bonding between the raw material composition and other substances can be suppressed. From these viewpoints, the hardness of the raw material composition is preferably 0.5g or more and 500g or less, more preferably 5g or more and 350g or less, even more preferably 15g or more and 250g or less, and even more preferably 15g or more and 150g or less. The hardness of the raw material composition is measured by the method described in the examples.
[0045] 〔powder〕 The ratio of the powder used in step 3 to the mass of solid particles (powder adhesion rate) is preferably 5% by mass or more, more preferably 7.0% by mass or more, even more preferably 7.5% by mass or more, and even more preferably 8.0% by mass or more, from the viewpoint of adhesion resistance and transport resistance. Furthermore, from the viewpoint of not affecting the feel of use, it is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, even more preferably 13% by mass or less, and even more preferably 12% by mass or less.
[0046] The powder can be any powder commonly used in cosmetics without any particular restrictions, and may be an inorganic powder or an organic powder. Inorganic and organic powders may be used in combination, but it is preferable to include an inorganic powder, more preferably an inorganic pigment, and even more preferably silica. Specifically, the same powder components as those contained in the aforementioned raw material composition can be used.
[0047] Preferably, the powder used is of a size that effectively prevents the solid particles, which are the target of the manufacturing method of the present invention, from adhering to other materials during the manufacturing process. For example, the size of the particles constituting the powder is such that the cumulative volume particle size D at 50% of the cumulative volume is measured by laser diffraction scattering particle size distribution analysis. 50 When expressed as, D50 The particle size is preferably 0.01 μm or larger, more preferably 0.1 μm or larger, even more preferably 1 μm or larger, even more preferably 5 μm or larger, and even more preferably 10 μm or larger. Using powder of this size makes the powder removal operation easy. Also, D 50 The particle size is preferably 500 μm or less, more preferably 300 μm or less, even more preferably 160 μm or less, even more preferably 100 μm or less, and even more preferably 30 μm or less. By using powder of this size, the powder can be easily attached to the surface of the granular raw material. Particularly D 50 Preferably, the particle size is 0.01 μm to 500 μm, more preferably 0.1 μm to 300 μm, even more preferably 1 μm to 160 μm, even more preferably 5 μm to 100 μm, and even more preferably 10 μm to 30 μm.
[0048] From the viewpoint of effectively preventing adhesion to other materials during the manufacturing process of solid particles, the oil absorption capacity of the powder is preferably 5 mL / 100g or more, more preferably 15 mL / 100g or more, and even more preferably 20 mL / 100g or more. Furthermore, from the viewpoint of preventing excessive absorption of oily components contained in the granular raw material into the powder, the oil absorption capacity of the powder is preferably 500 mL / 100g or less, more preferably 400 mL / 100g or less, and even more preferably 350 mL / 100g or less. The oil absorption capacity is measured in accordance with JIS K5101-13-1:2004.
[0049] The amount of powder in solid particles can be determined and measured by various methods. For example, if the powder is inorganic, it can be quantified by burning the organic matter in the solid particles using a differential thermogravimetric analyzer, as shown below, and measuring its remaining percentage. The amount of inorganic powder is measured by the method described in the examples.
[0050] If the powder is an organic substance, the sample is prepared by dissolving all the components of the solid particles in a solvent. 1 The amount of powder adhering to the core can be quantified by measurements such as H-NMR and laser desorption / ionization mass spectrometry (LDI-MS).
[0051] The solid particles produced by the manufacturing method of the present invention are preferably used as cosmetics. For example, they can be used in a cosmetic method in which the solid particles are crushed and applied to the human body for cosmetic purposes. Specifically, the solid particles can be placed on a cosmetic palette, crushed with a makeup brush, and then applied to the lips like lipstick using the makeup brush. Alternatively, the solid particles can be crushed on the back of the hand and applied to the cheeks with the fingers like blush or concealer. Alternatively, the solid particles can be crushed on the back of the hand and applied to the fingers or the back of the hand like hand cream. Furthermore, the solid particles can be crushed by hand and used like an oil cleanser. Furthermore, the solid particles can be crushed with hands or tools and applied to the hair, and used like a treatment or hair wax.
[0052] Although the present invention has been described above based on its preferred embodiments, the present invention is not limited to the above embodiments. [Examples]
[0053] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to these examples.
[0054] [Preparation of raw material composition] Table 1 below shows the composition of the raw material composition for lipstick, and Table 2 shows the composition of the raw material composition for eyeshadow. For both raw material compositions, the base raw material (raw material composition excluding coloring pigments and extender pigments) was heated and dissolved at 110°C for 30 minutes and uniformly mixed with a disperser. Next, the coloring pigments and extender pigments were added to the base raw material and uniformly mixed for a further 15 minutes, and after degassing, the raw material composition was prepared by solidifying by natural cooling. The melting points of the prepared raw material compositions were measured according to the general test method for quasi-drug raw material standards, and were found to be 70°C for the raw material composition for lipstick and 79°C for the raw material composition for eyeshadow.
[0055] The lipstick raw material composition prepared above was heated and melted at 115°C, and then filled into a resin ointment jar (30 mm in diameter, 14 mm in height) to a height of 10 mm. After cooling and solidifying at 20°C for 2 hours and standing at 30°C for 6 hours or more, the hardness of the lipstick raw material composition was measured using a rheometer manufactured by Rheotec, by reading the maximum load when a jig with a diameter of φ2 mm was inserted to a depth of 2 mm at a table speed of 2 mm / s. The hardness of the lipstick raw material composition was found to be 35 g. When the eyeshadow raw material composition prepared above was measured under the same conditions, its hardness was 41 g.
[0056] [Table 1]
[0057] [Table 2]
[0058] As shown in Table 1, the amount of oily components in the raw material composition was 89.4% by mass of the components indicated as the base material, and the amount of powdery components was 10.6% by mass of the total amount of coloring pigments and extender pigments. Furthermore, the amount of oily components in the raw material composition with a melting point above 20°C (solid at 20°C) was 8% by mass of the total amount of paraffin, polyethylene wax, and microcrystalline wax, and the amount of oily components with a melting point of 20°C or lower (liquid at 20°C or lower) was 81.4% of the total amount of other components. As shown in Table 2, the amount of oily components in the eyeshadow raw material composition was 79.45% by mass of the components indicated as the base material, and the amount of powdery components was 20.55% by mass of the total amount of coloring pigments, extender pigments, and dispersants. Furthermore, the amount of oily components in the eyeshadow raw material composition with a melting point above 20°C (solid at 20°C) was 9.0% by mass of the total amount of paraffin, synthetic wax, and microcrystalline wax, and the amount of oily components with a melting point of 20°C or less (liquid at 20°C or less) was 70.45% by mass of the total amount of other components.
[0059] [Example 1] Processes 1 and 2 (Production of granular raw materials) Multiple granular raw materials 13 were obtained from a lipstick raw material composition using the apparatus shown in Figure 1. Specifically, the lipstick raw material composition 10, which had been given fluidity by heating and melting the raw material composition to 90°C, was pumped using a pump 11 and dispensed from the tip of a nozzle 12 with an inner diameter of 2.0 mm at the dropping temperature and dropping distance described in Table 3 to produce granular raw materials 13 as liquid droplets. The dropping distance is the distance between the tip of the nozzle 12 and the outermost surface of the powder layer 14.
[0060] Step 3 (Contact between granular raw material and powder) The granular raw material 13 discharged as described above is subjected to a vibration feeder 19 (a small electromagnetic feeder CF-2 manufactured by Sinfonia Technology Co., Ltd.) equipped with a vibration device 15 and a trough 16. A 10 mm thick layer of powder 14 at a temperature of 25°C, with vibrations of 0.663 mm amplitude and 54.0 Hz, is supplied and dropped onto the trough 16 (dropping distance 117 mm), causing the granular raw material 13 to come into contact with the powder 14 and the powder 14 to adhere to the surface of the granular raw material 13. The contact time shown in Table 3 is the time from the dropping of the granular raw material 13 until the granular raw material 13 with the powder 14 attached reaches the outlet of the trough 16. The powder 14 has an average particle size of D 50 Spherical silica with a diameter of 15 μm and an oil absorption capacity of 150 mL / 100 g was used. This caused the powder 14 to adhere to the surface of the target granular raw material 13, thereby obtaining solid particles 1 for lipstick in which the granular raw material 13 was coated with powder 14. The amplitude values listed in Table 3 were measured using a laser displacement meter (Keyence LK-G5000) at the top surface of the trough 16, directly above the vibration device 15. The measurement conditions were diffuse reflection mode, sampling period of 200us (5kHz), and moving average of 4. In addition, the amplitude was also measured visually using an amplitude nameplate only in Example 1. The amplitude nameplate was attached to the center of the side of the trough 16, and the scale at the point where the diagonal lines intersected was read visually as 1 mm, which was a different value from the measurement by the laser displacement meter. The amplitude on the trough is small directly above the vibrating device and becomes larger towards the tip of the trough, which is further away from the vibrating device. However, the center of the trough where the vibration nameplate was attached was a part that was slightly away from the vibrating device, so it is thought that the value was larger than the value measured by the laser displacement meter.
[0061] (Removal of powder and cooling) Subsequently, the powder 14 and solid particles 1 were separated using a sieve 17 with a mesh size of 2,000 μm at room temperature (25°C), and any powder 14 that was not attached was removed. The solid particles 1 were allowed to cool naturally on the sieve for more than 1 minute and then collected. The average projected area of the solid particles 1, calculated from 10 randomly selected solid particles 1, was 11 mm². 2 The average diameter was 3.7 mm and the average height was 2.4 mm.
[0062] [Evaluation of solid particles 1] (1) Evaluation of adhesion resistance 0.5 g of the obtained solid particles 1 were filled into a glass screw tube No. 02 (manufactured by Maruemu, with an inner diameter of 5.5 mm at the mouth, a height of 35 mm, and a height of 40 mm after capping) as a container, and the height X (cm) of the solid particles from the bottom to the top of the container was measured. The container was then left to stand at 50°C for 60 minutes, and then left at room temperature (25°C) for 1 minute. After that, the container was inverted, and the height Y (cm) of the solid particles that adhered to the bottom of the upper container and did not fall to the lid of the lower container was measured. Based on these results, the adhesion rate (%) of the solid particles was calculated using the following formula 1. A smaller value indicates higher adhesion resistance. Note that if all the solid particles adhere to the bottom of the container, and gravity is stronger than the adhesive force, the value of Y when the container is inverted may exceed the initial value of X, resulting in an adhesion rate exceeding 100%. In comparative examples 1-3 in Table 3, all solid particles adhered to the bottom of the container. Adhesion rate (%) = Y / X × 100 (Equation 1) (2) Evaluation of user experience The obtained solid particles 1 were crushed in the hand to check for any roughness originating from the powder 14, and it was found that there was no roughness, resulting in a good feel during use. (3) Evaluation of transport tolerance 0.5 g of the obtained solid particles 1 were filled into a glass screw tube No. 02 (manufactured by Maruemu, with an inner diameter of 5.5 mm at the mouth, a height of 35 mm, and a height of 40 mm after capping) as a container, and the height X (cm) of the solid particles from the bottom to the top of the container was measured. A resin cylinder with an inner diameter of 25 mm and a height of 116 mm was placed vertically on a non-slip mat (material: polyethylene, thickness: 5 mm), and the container was dropped from above in an upright position at room temperature (25°C) (drop distance: 112 mm). After dropping each container 8 times, the container was inverted, and the height Y (cm) of the solid particles that adhered to the bottom of the upper container and did not fall to the lid of the lower container was measured, and the "adhesion rate" was calculated using the above (Equation 1). A smaller value indicates higher transport resistance. In evaluating transport resistance, the process of dropping the solid particles after filling the container may cause the particles to be slightly crushed or the gaps between particles to become clogged due to the impact. Therefore, even if all the solid particles adhere to the bottom of the container, the Y value when the container is inverted may be lower than the initial X value, resulting in an adhesion rate of less than 100%. In comparative examples 1-3 in Table 3, all the solid particles adhered to the bottom of the container. (4) Determination of powder adhesion rate The amount of silica (adhesion rate) used as powder 14 in solid particle 1 was quantified as follows. The obtained solid particles 1 were heated from 25°C to 600°C at a rate of 10°C / min under a differential thermogravimetric analyzer TG-DTA EXSTAR 6200 manufactured by Hitachi High-Tech Science Corporation, with an air supply of 200 mL / min, and the mass of the residue after combustion was measured. The powder adhesion rate was calculated using the following formula from the mass of the residue when the same treatment was performed using only the same mass of raw material composition as that used to produce solid particles 1. The results are shown in Table 3. (Powder adhesion rate (mass%)) = (Mass of residual solid particle 1%) - [(Mass of residual raw material composition%) ÷ [100 - (Mass of residual raw material composition%)]] × [100 - (Mass of residual solid particle 1%)] (5) Mass of solid particles Ten solid particles were randomly selected from the obtained solid particle 1, and their masses were measured. The number-average masses of the ten particles are shown in Table 3. (6) Strength of solid particles Ten particles were randomly selected from the obtained solid particles 1. Using a modular compact rheometer MCR-302 manufactured by Anton Paar Japan Co., Ltd., the particles were crushed on a φ25 mm parallel plate at a descent speed of 20 μm / s, and the strength of the particles was measured by reading the collapse point from the load and displacement values. The number-average strengths of the ten particles are shown in Table 3. (7) Observation of the cross-section Two solid particles were randomly selected from the obtained solid particle 1, and each solid particle 1 was cut in half with a knife. The cross-sections were observed using a scanning electron microscope VE-7800 manufactured by Keyence Corporation. Images were taken of four locations (top, bottom, left, and right) of the cross-section of each particle. The thickness of the shell portion, which consists of the raw material composition incorporating the powder covering the surface of the core portion, was measured at three locations for each image, for a total of 12 locations per particle. The average thickness of the shell portion at a total of 24 locations was calculated and is shown in Table 3. Furthermore, as shown in Figure 3, the powder was not only attached to the surface of the solid particle 1, but was also incorporated into the raw material composition from the surface of the core portion to a thickness of approximately 100 to 200 μm.
[0063] [Examples 2-5] Except for changing the conditions of the manufacturing method as shown in Table 3, solid particles 1 for lipstick were manufactured in the same manner as in Example 1. The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3.
[0064] [Example 6] In Example 7, the vibrating device 15 and trough 16 used in Example 1 were replaced with a bowl feeder 20 (parts feeder ER-30BR manufactured by Sinfonia Technology Co., Ltd.) equipped with a vibrating device 15 and a bowl 18, and the conditions of the manufacturing method were changed as shown in Table 3. Otherwise, solid particles 1 for lipstick were manufactured in the same manner as in Example 1. The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3. Note that the contact time in Example 7 is the time from when the granular raw material 13 is dropped until the granular raw material 13 with the powder 14 attached reaches the outlet of the bowl 18.
[0065] [Example 7] Powder 14, average particle size D 50 Solid particles 1 for lipstick were manufactured in the same manner as in Example 1, except that the mixture was changed to a mixture of spherical silica (MetaShine MT1080TY, manufactured by Nippon Sheet Glass Co., Ltd.) with a diameter of 15 μm and an oil absorption capacity of 150 mL / 100 g (spherical silica:pigment = 9:1). The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3.
[0066] [Example 8] Solid particles 1 for lipstick were manufactured in the same manner as in Example 1, except that the raw material composition was changed to a raw material composition for eyeshadow. The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3.
[0067] [Comparative Example 1] The contact between the granular raw material and the powder was modified in the same manner as in Example 1. The granular raw material 13 was dropped onto the powder 14, which had been left to stand, at room temperature (25°C). The powder was then made into a fluid state using a stirring means consisting of anchor blades, allowing the powder 14 to adhere to the surface of the granular raw material 13 for 60 seconds, followed by 1 minute of natural cooling. Otherwise, solid particles 1 for lipstick were produced in the same manner as in Example 1. The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3.
[0068] [Comparative Example 2] and [Comparative Example 3] Powder 14 was spread to a thickness of 10 mm in a balance dish (BDA-3 manufactured by AS ONE Corporation), granular raw material 13 was dropped onto the powder 14 at room temperature (25°C), and natural cooling was allowed for 1 minute. For Comparative Example 2, the contents of the balance dish were sieved, and for Comparative Example 3, the particles were collected using a spatula and sieved, but otherwise, solid particles 1 for lipstick were produced in the same manner as in Example 1. The results of evaluating the obtained solid particles 1 in the same manner as in Example 1 are shown in Table 3.
[0069] [Table 3]
[0070] As shown in Table 3, both the solid particles 1 of the example and the solid particles of the comparative example exhibited good usability because the core portion, which consists of a raw material composition containing oily components, is covered with a shell portion containing silica as powder. Furthermore, the solid particles 1 of the example all exhibited good adhesion resistance and good transport resistance. On the other hand, the solid particles of the comparative example had low average particle strength and did not have sufficient adhesion resistance or transport resistance. This is thought to be because, in the solid particles 1 of the example, not only did silica adhere to the surface, but as shown in Table 3 and Figure 3, silica was incorporated into the raw material composition at a high density and uniform thickness from the surface of the core portion to about 110 μm to 200 μm. In contrast, in the solid particles of the comparative example, as shown in Figure 4, it was found that the silica adhering to the surface was not of uniform thickness, and there were areas where almost no silica was adhering. [Explanation of symbols]
[0071] 1 solid particles 10. Raw material composition with imparted fluidity 11 pumps 12 nozzles 13 Granular raw materials 14 Powder 15 Vibration device 16 Trough 17 Sieve 18 bowls 19. Vibratory feeder 20 Bowl Feeders
Claims
1. A method for producing solid particles comprising the following steps 1 to 3: Step 1: A step of heating a raw material composition containing an oily component to impart fluidity; Step 2: granulating the raw material composition having been given fluidity to obtain a granular raw material; Step 3: contacting the granular raw material with a powder to coat the surface of the granular raw material with the powder; The method for producing solid particles, wherein the contact is performed while the powder is vibrated.
2. The method for producing solid particles according to claim 1 , wherein the powder comprises a pigment.
3. The method for producing solid particles according to claim 1 or 2, wherein the powder contains silica.
4. The method for producing solid particles according to claim 1 or 2, further comprising a step of cooling the particulate raw material.
5. The method for producing solid particles according to claim 1 or 2, further comprising a step of removing the unattached powder.
6. The method for producing solid particles according to claim 1 or 2, wherein the granular raw material in step 2 is obtained by heating the raw material composition to a melting point or higher.
7. The method for producing solid particles according to claim 1 or 2, wherein the vibration has an amplitude of 0.3 mm or more and a frequency of 30 Hz or more.
8. The average particle size D of the powder 50 The method for producing solid particles according to claim 1 or 2, wherein the average particle diameter is 0.01 μm or more and 500 μm or less.
9. The method for producing solid particles according to claim 1 or 2, wherein the average mass per particle of the obtained solid particles is 1 mg or more and 10,000 mg or less.
10. A solid particle having a core portion made of a raw material composition and a shell portion covering at least a part of the surface of the core portion, The shell portion is made of a raw material composition incorporating a powder, and the thickness of the raw material composition incorporating the powder is 110 μm or more.
11. The solid particles according to claim 10, which are for use in cosmetics.